Real-World effectiveness of eculizumab in atypical hemolytic uremic syndrome: a retrospective study from Western China - Hu, Yun; Zhang, Yanyan; Wang, Wei; Li, Guisen; Chen, Shasha (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the real-world efficacy and safety of eculizumab in atypical hemolytic uremic syndrome (aHUS) within a Western Chinese cohort, with emphasis on treatment initiation timing and renal outcomes.MethodsWe conducted a retrospective analysis of 17 aHUS patients treated at Sichuan Provincial People’s Hospital, focusing on the relationship between treatment timing and clinical prognosis. To evaluate timing effects, patients were categorized as Early Initiators (treatment within 7 days of symptom onset, n=9) versus Delayed Initiators (treatment beyond 7 days, n=8) The main outcome measures included hematological parameters, renal function, and adverse events.ResultsThe cohort (n=17, 76.5% female, mean age 43.2 ± 20.0 years) demonstrated significant improvements post-eculizumab: creatinine decreased from 647.0 (439.0, 915.0) to 198.5 (86.5, 749.5) μmol/L, eGFR increased from 8.0 (5.0, 11.0) to 22.1 (6.4, 55.1) mL/min/1.73m², platelets rose from 75 ± 11 to 143 ± 33×109/L, and LDH declined from 787.5±908.0 to 232.8 ± 70.0 U/L (all P<0.001). Early treatment initiation (≤7 days, n=9) yielded superior outcomes versus delayed (>7 days, n=8): higher renal remission (88.9% vs 12.5%, P=0.003), hematological remission (100% vs 12.5%, P<0.001), and reduced dialysis dependence (0% vs 87.5%, P<0.001), with greater ΔeGFR (+(19.5 ± 3.1) vs +(2.3 ± 1.7 )mL/min/1.73m2, P=0.016) and Δplatelets (+(67.8 ± 9.8) vs +(19.3 ± 7.2)×109/L, P=0.007). Renal survival favored early treatment (log-rank P<0.001), though residual renal impairment persisted. Two non-meningococcal bloodstream infections resolved with antibiotics.ConclusionOur findings provide the first Chinese evidence supporting early eculizumab initiation (≤7 days post-symptom onset) significantly improves hematological/renal outcomes and reduces dialysis dependence in Chinese aHUS patients. Despite residual renal impairment, prompt complement blockade mitigates ESRD risk, supporting time-sensitive intervention in resource-limited settings.